2020
DOI: 10.4103/meajo.meajo_182_19
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of keratoconus in refractive surgery cases in Western India

Abstract: Purpose: To report the prevalence of keratoconus (KCN) in patients presenting for refractive surgery in western India. METHODS: A cross-sectional, observational, retrospective study performed at a tertiary eye care center. A total of 2902 cases, aged 18–40 years who presented in the refractive surgery department between January 2014 and December 2018 were included. Records of all the included cases were reviewed. Patients showing KCN pattern on topography were noted and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
0
4
1
Order By: Relevance
“…25 A comparable disease prevalence (pooled 2.3%; range: 0.9% to 2.4%) has been found in India. 13,26,27 A significantly higher prevalence than reported in this study was found in Saudi Arabia, Iran and Africa. 13,16,28 In a prospective, observational, multicenter study, the keratoconus prevalence was 4.8% in a pediatric population ( n = 522) living in Riyadh 28 ; it was 3.6% in a large population-based study in Iran ( n = 3314).…”
Section: Discussioncontrasting
confidence: 57%
“…25 A comparable disease prevalence (pooled 2.3%; range: 0.9% to 2.4%) has been found in India. 13,26,27 A significantly higher prevalence than reported in this study was found in Saudi Arabia, Iran and Africa. 13,16,28 In a prospective, observational, multicenter study, the keratoconus prevalence was 4.8% in a pediatric population ( n = 522) living in Riyadh 28 ; it was 3.6% in a large population-based study in Iran ( n = 3314).…”
Section: Discussioncontrasting
confidence: 57%
“…The pathfinder corneal analysis detection system in the Atlas topographer shows keratoconus pattern probability of ≥40% along with an anterior elevation of ≥12 μm and a posterior elevation of ≥25 μm on the Scheimpflug analyzer. 15,16 The eyes showing keratoconus probability on pathfinder corneal analysis with anterior elevation <12 μm and posterior elevation <25 μm on the Scheimpflug analyzer without clinical signs were considered as suspected cases and those with no clinical and topographical signs as forme fruste ectasia. 15,16 The pathfinder corneal analyzer was described in a previous article.…”
Section: Methodsmentioning
confidence: 99%
“…15,16 The eyes showing keratoconus probability on pathfinder corneal analysis with anterior elevation <12 μm and posterior elevation <25 μm on the Scheimpflug analyzer without clinical signs were considered as suspected cases and those with no clinical and topographical signs as forme fruste ectasia. 15,16 The pathfinder corneal analyzer was described in a previous article. 15 The pattern analysis included only the right eyes of patients with clinical ectasia.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations